Conservative treatment of postintubation tracheal laceration with pneumomediastinum, bilateral pneumothorax, and massive subcutaneous emphysema - Romic, Marijan (Lung India, 2021)
Postintubation tracheal laceration (PITL) is a rare, potentially life-threatening complication requiring prompt diagnosis and treatment. Patients typically present with subcutaneous emphysema and pneumomediastinum, whereas concomitant pneumothorax is rarely reported. A conservative treatment is indicated in selected respiratory stable patients with small lacerations. Herein, we reported an unusual case of PITL with bilateral pneumothorax that was treated with chest tube drainage and conservative measures in the intensive care unit. The key success of the PITL management is early recognition of signs and symptoms and an adequate selection of management approaches.